2007
DOI: 10.1021/jm0700060
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Recombinant Cytochrome P450 Isoforms 2D6 and 2C9 by Diverse Drug-like Molecules

Abstract: The affinities of a diverse set of 500 drug-like molecules to cytochrome P450 isoforms 2C9 and 2D6 were measured using recombinant expressed enzyme. The dose-response curve of each compound was fitted with a series of equations representing typical or various types of atypical kinetics. Atypical kinetics was identified where the Akaike Information Criterion, plus other criteria, suggested the kinetics was more complex than expected for a Michaelis-Menten model. Approximately 20% of the compounds were excluded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…This could be explained by non-genetic factors having been shown to reduce CYP2D6 expression and/or activity. 17,18 On the other hand, limitations in phenotype measurement could also contribute to these discrepancies. Indeed, in contrast to the PM phenotype, where a DEM MR antimode can be precisely defined, the definition for the IM and UM phenotype is less clear.…”
Section: Genotype-phenotype Associationmentioning
confidence: 99%
“…This could be explained by non-genetic factors having been shown to reduce CYP2D6 expression and/or activity. 17,18 On the other hand, limitations in phenotype measurement could also contribute to these discrepancies. Indeed, in contrast to the PM phenotype, where a DEM MR antimode can be precisely defined, the definition for the IM and UM phenotype is less clear.…”
Section: Genotype-phenotype Associationmentioning
confidence: 99%
“…Non-MM or atypical saturation kinetics occurs when an enzyme-substrate-substrate (ESS) complex is formed (Korzekwa et al, 2014b). CYP2C9 has been shown to display multisubstrate interactions approximately 20% of the time, whereas CYP2D6 was almost always competitive (McMasters et al, 2007). Although a similar study has not been reported for CYP3A4, the numerous reports of CYP3A4 non-MM kinetics suggest that multisubstrate interaction kinetics is common (Wrighton et al, 2000).…”
Section: Introductionmentioning
confidence: 97%
“…This results in some unusual kinetics, presumably due to simultaneous interaction of multiple substrates or inhibitors with the active site (Huang et al, 1981;Lasker et al, 1982;Atkins, 2005;McMasters et al, 2007). Non-MM or atypical saturation kinetics occurs when an enzyme-substrate-substrate (ESS) complex is formed (Korzekwa et al, 2014b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although none of the five TDIs here contains methylenedioxy groups, one such published dataset was evaluated, namely inhibition of CYP2D6 by methylenedioxymethamphetamine (Heydari et al, 2004). It was anticipated that this dataset would have an MM base because CYP2D6 is unlikely to display EII binding kinetics (McMasters et al, 2007). Analysis by the MM-only and MM-quasi-irreversible models is shown in Fig.…”
Section: Discussionmentioning
confidence: 99%